COVID-19 in Pregnancy: Occupations With Higher Density of Population Exposure Associated With More Severe Disease. Issue 12 (December 2021) - Miracle, Jill E.; Ganesh, Prakash R.; Rose, Johnie; Terebuh, Pauline; Stange, Kurt C.; Wolfe, Honor M.; Szabo, Andrea; Gullett, Heidi; Pope, Rachel
Abstract : Objective: To define the symptomatology of SARS-CoV-2 infection in pregnancy and associations between occupation, sociodemographic factors, and comorbidities with the severity of COVID-19 disease in pregnancy in all trimesters, regardless of hospitalization. Methods: We studied a retrospective cohort of a public health surveillance sample of persons with COVID-19 infection diagnosed during pregnancy. Data was collected March 2020 to August 2020 regarding symptoms, disease severity, comorbidities, obstetric history, and occupation. Results: One hundred sixty-three individuals were identified. Constitutional (64%) and lower respiratory symptoms (61%) were most common. Seventeen individuals (13.6%) were hospitalized, and one person (0.7%) died due to COVID-19. Risk factors for severe disease were age and an occupation that had high intensity exposure to people. Conclusions: Occupational exposure is a risk factor for severe COVID-19 disease in pregnancy, justifying policy measures to ensure protection of this vulnerable population.